Consistent life history shifts along invasion routes? An examination of round goby populations invading on two continents. Issue 6 (20th February 2018) - Masson, L.; Masson, G.; Beisel, J. N.; Gutowsky, L. F. G.; Fox, M. G.
Abstract: Aim: Many invasive populations exhibit dynamic life history shifts along their invasion route. We investigated whether these shifts represent consistent biological responses of a given species to range expansion, even in systems located in different geographic regions. Location: North‐eastern France, Central Ontario (Canada). Method: We investigated population density, life history traits and age‐specific reproductive investment in expanding populations of round goby at three invasion stages (expansion front, area colonized one year earlier and area colonized for ~five years) along the invasive routes in two river systems differing in climate and system productivity. Interindividual variability, shown to affect range expansion rates, was also investigated along the invasion routes. The study was based on female round gobies collected in three locations within each invasion stage twice monthly throughout the reproductive season (March/May to July). Results: In both systems, reproductive investment was highest in the newly colonized area and decreased with time since colonization. A faster decrease in reproductive investment was found in the warmer, more productive system behind the invasion front, potentially associated with faster population growth and increased intraspecific competition. In both systems, individual variability in growth and reproductive traits increased from the newly colonized area to the areas of earlier colonization. Main conclusions: The patterns observed in the two systems suggest a common invasion strategy independent of environmental conditions and highlight the dynamic nature of invasive populations' life history behind the invasion front. Common energetic allocation strategies can be expected at the invasion front. Range expansion may be associated with population growth induced by rapid acclimation to biotic conditions associated with range shift.